Secular Stagnation, Financial Frictions, and Land Prices - Zhifeng Cai (Rutgers University, Department of Economics, 2020)
This paper explores a model in which large transitory financial shocks can generate persistent slumps in output, land prices, and interest rate. The propagation originates from high sensitivity of land prices with respect to fundamental, which is achieved by a land consumption channel that exploits the high complementarity of land services and consumption in households' preference. When this complementarity is disciplined by micro-level evidence, the unique recursive equilibrium features an S-shaped law of motion for capital with two locally stable steady states. Small shocks move the economy around the unconstrained steady state whereas large transitory financial shocks push the economy into the constrained steady state at which low interest rate makes firm unwilling to save out of the financial friction, leading to a secular stagnation.
Keywords: E0; 330; Secular Stagnation; Steady-State Multiplicity; Financial Frictions; House Prices